Braincase anatomy of Pterodaustro guinazui, pterodactyloid pterosaur from the Lower Cretaceous of Argentina - Codorniú Dominguez, Laura Susana (2016)
The braincase anatomy of pterosaurs is poorly known because this region of the skull is rarely preserved, particularly in basal pterodactyloid pterosaurs (Archaeopterodactyloidea). We present new information on the braincase morphology of the Early Cretaceous Argentinean ctenochasmatid Pterodaustro guinazui. Morphological information collected from several specimens permits the description of many features of this area of the skull for the first time. The braincase of Pterodaustro is characterized by a skull roof with subtriangular, elongated frontals and rounded, posteroventrally oriented parietals; low nuchal crest; ossified ethmoidal elements; ossified interorbital septum; short and fan-shaped paroccipital processes with undulating lateral and medial surfaces; occipital condyle formed mainly by the exoccipitals; fork-shaped basioccipital; long, anteroventrally directed basisphenoid body with keeled ventral surface and short basipterygoid processes; well-developed rostral tympanic recess; rod-like columella; and separate foramina for cranial nerves XII and IX-XI within a common subdivided recess. We were able to identify foramina for cranial nerves II, V, VI, and VII; vascular foramina, such as the caudal middle cerebral vein, the dorsal head vein, and the internal carotid artery; and the columellar recess. This research reveals many features of the braincase of Pterodaustro-some of which are considered potential autapomorphies-for the first time. It also provides new insights into the neurocranial anatomy of pterosaurs, and in turn, contributes to the understanDing of the evolution of the braincase in Pterosauria.Citation for this article: Codorniú, L., A. Paulina-Carabajal, and F. A. Gianechini. 2015. Braincase anatomy of Pterodaustro guinazui, pterodactyloid pterosaur from the Lower Cretaceous of Argentina.